2014
DOI: 10.1093/medlaw/fwu008
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Competition Principles Into Health Care Through EU Law And Policy: A Case Study of the Netherlands

Abstract: A national health care service is one of the central pillars of the welfare state in Europe. Recent moves to modernise health care, alongside introducing efficiencies through competition have resulted in experimentation and a re-organisation of national health care systems. The experimental nature of the reforms has brought health care into the focus, but uncertain territory, of EU economic law, especially competition law. Added to these pressures, the new EU fiscal measures oblige Member States to avoid exces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Thus, although both the Netherlands and England have recently instituted reforms thought to trigger application of the competition rules, how these are being applied varies considerably, in part due to there being greater scope for competition in a Bismarck rather than a Beveridge system. 81 The resulting scope for potential legal uncertainty has been described in terms of emerging 'Euro-national competition rules', 82 as distinct from a process of 'spontaneous harmonization' as Member States experiment with varying degrees of private provision and competition in their healthcare systems.…”
Section: Overview Of the Legal Basis And Scope Of Article 168(1)-(6) mentioning
confidence: 99%
“…Thus, although both the Netherlands and England have recently instituted reforms thought to trigger application of the competition rules, how these are being applied varies considerably, in part due to there being greater scope for competition in a Bismarck rather than a Beveridge system. 81 The resulting scope for potential legal uncertainty has been described in terms of emerging 'Euro-national competition rules', 82 as distinct from a process of 'spontaneous harmonization' as Member States experiment with varying degrees of private provision and competition in their healthcare systems.…”
Section: Overview Of the Legal Basis And Scope Of Article 168(1)-(6) mentioning
confidence: 99%
“…In Home Care Kennemerland, the Rotterdam district court held that "strong indications" showed that the institutions did not compete within the relevant market that comprised both working areas [33]. Legal commentators have welcomed both judgments since they would (merely, EL) urge ACM to more carefully examine the factual and legal context when examining competition cases in healthcare [34][35][36]. Obviously, careful contextual analysis is a prequisite for good decision-making.…”
Section: Antitrust Enforcement Regarding the Provision Of Psychologicmentioning
confidence: 99%
“…However, this degree of freedom has long been deemed circumscribed: market-based reforms may have the unintended consequence of triggering the applicability of EU competition law (Prosser, 2010). At EU level, the possibility of divergent interpretations by National Competition Authorities raises concerns about consistency at EU level, potentially creating "Euro-national competition rules for healthcare" (van de Gronden, 2011; van de Gronden and Szyszczak, 2014). The need for direction and guidance to be set at EU level is also important because we know that England (UK) and the Netherlands -the two Member States to engage most actively with competition reforms of their healthcare systems -have created regimes which are heavily influenced by, and even borrow terminology from, EU competition law (Guy, 2019).…”
Section: Introductionmentioning
confidence: 99%